100 things you should know about Planet Earth - Riley, Peter; Miles Kelly Publishing; Carpenter, Clive (Miles Kelly Publishing Limited: Essex, 2004)
This title leads children through the amazing natural features of our planet, discovering violent volcanoes, massive mountains and mighty oceans.
Keywords: Earth sciences